PEANUT SUPPLY CHAIN ANALYSIS IN WEST ACEH REGENCY - Akmal, Heri; Mustafa; Zakiah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Peanuts in West Aceh District peanuts are one of the leading commodities of peanut farmers' income. With a harvest area of ​​240.00 hectares and production of 527.00 tons per year. The aim of this research is to analyze the supply chain of peanuts for consumption in West Aceh District. The results of the research using the Food Supply Chain Network (FSCN) approach, it can be concluded that the supply chain for peanuts for consumption already has clear targets, the relationship between actors is structured, but has not been managed properly in terms of business processes that have not been integrated in the long term. In peanuts, the seeds of collaboration between actors have been well established in terms of information disclosure, cooperation and integration between supply chain actors. Besides that, business processes run structured with good management. The results of supply chain performance analysis through the farmer's share received by farmers in each channel where the value of the farmer's share in peanuts for channel 1 is 46.88 percent, channel 2 is 45.45 percent and channel 3 is 50.00 percent. Based on these results, it can be concluded that the peanut supply chain for channel 3 is more efficient than the peanut supply chain for channels 1 and channel 2.